2006
DOI: 10.1074/jbc.m607281200
|View full text |Cite
|
Sign up to set email alerts
|

Saposin A Mobilizes Lipids from Low Cholesterol and High Bis(monoacylglycerol)phosphate-containing Membranes

Abstract: Saposin A (Sap-A) is one of five known sphingolipid activator proteins required for the lysosomal degradation of sphingolipids and for the loading of lipid antigens onto antigen-presenting molecules of the CD1 type. Sap-A assists in the degradation of galactosylceramide by galactosylceramide-␤-galactosidase in vivo, which takes place at the surface of intraendosomal/intralysosomal vesicles. Sap-A is believed to mediate the interaction between the enzyme and its membrane-bound substrate. Its dysfunction causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 55 publications
2
58
0
Order By: Relevance
“…8 ). These fi ndings confi rm earlier observations on the essential functions of Sap A and Sap B, for the glycosphingolipid metabolism, that are impaired by high cholesterol levels ( 7,8 ). Furthermore, it was shown that a defect of the protein NPC2 in Niemann-Pick disease type C not only caused an accumulation of cholesterol in the liver and brain, but also, as a secondary effect, caused increased storage of gangliosides such as GM2 ( 74,75 ).…”
Section: The His 6 -Tag Changes the Overall Properties Of Gm2apsupporting
confidence: 88%
See 1 more Smart Citation
“…8 ). These fi ndings confi rm earlier observations on the essential functions of Sap A and Sap B, for the glycosphingolipid metabolism, that are impaired by high cholesterol levels ( 7,8 ). Furthermore, it was shown that a defect of the protein NPC2 in Niemann-Pick disease type C not only caused an accumulation of cholesterol in the liver and brain, but also, as a secondary effect, caused increased storage of gangliosides such as GM2 ( 74,75 ).…”
Section: The His 6 -Tag Changes the Overall Properties Of Gm2apsupporting
confidence: 88%
“…This favors an electrostatic binding of the positively charged activator proteins and the polycationic hydrolases, and enhances degradation of (glyco)sphingolipids substantially ( 7,9,10,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Two recent reports have shown that glycosylated recombinant saposins A (37) and B (38) expressed in yeast differ from the unglycosylated forms in their ability to solubilize lipids from immobilized liposomes. However, earlier reports have shown that nonglycosylated saposins retain their lipid-binding and enzyme activation effects (39), and recombinant sapC expressed in Escherichia coli was shown to have similar properties to sapC purified from natural tissues (40).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of saposins as lipid transfer proteins independently of any storage phenotype, we designed cell-free assays and measured binding of Escherichia coli-purified recombinant saposins to synthetic lipids and subsequent loading of CD1d molecules. Although there is evidence that glycosylation influences the ability of recombinant saposins to mobilize lipids from membranes and liposomes (51,52), nonglycosylated proteins have been shown to retain comparable lipid binding and hydrolase-activating capacity. Despite high homology, the four saposins have different lipid specificities, as demonstrated by the phenotype of patients with selective deficiency of individual molecules (53).…”
Section: Discussionmentioning
confidence: 99%